2022
DOI: 10.3390/molecules27061951
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anti-Skin-Aging Activity of Yeast Extract-Treated Resveratrol Rice DJ526

Abstract: Resveratrol is a powerful antioxidant that defends against oxidative stress in cells but is not found in large quantities in plants. Resveratrol-enriched rice DJ526, which was developed as a functional crop, shows a diverse range of biological activities. Resveratrol production is measured as total resveratrol and its glycoside, piceid, which is mainly found in plant-derived resveratrol. In the present study, elicitation using yeast extract (YE), methyl jasmonate, and jasmonic acid increased resveratrol produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Its underlying mechanisms might be associated with the extracellular purinergic signaling pathway (Zhu et al, 2022). Otherwise, scientists (Kantayos et al, 2022) found that the pretreatment with yeast extracts (YEs) could enhance the antioxidant activity of resveratrol, and following its antioxidant capacity measurement confirmed that YEs‐pretreated resveratrol effectively increased its antioxidant capacity from 3.9% to 94.3%, thus reducing the wound gap in HaCaT cells, with a maximum rate of 60.2% after 24 h and complete closure after 48 h. To maximize its antioxidant property, resveratrol was incorporated into microparticles (size ranging between 20 and 30 μm) through spray drying to treat diabetic wounds. Eroğlu et al (2015) showed that resveratrol‐loaded hyaluronic acid (HA)‐dipalmitoyl phosphatidylcholine (DPPC) microparticles could increase the cell proliferation of human dermal fibroblast cells, which might be related to increase glutathione (GSH)/oxidized glutathione (GSSG) ratio.…”
Section: Beneficial Effects and Underlying Mechanisms Of Resveratrol ...mentioning
confidence: 99%
“…Its underlying mechanisms might be associated with the extracellular purinergic signaling pathway (Zhu et al, 2022). Otherwise, scientists (Kantayos et al, 2022) found that the pretreatment with yeast extracts (YEs) could enhance the antioxidant activity of resveratrol, and following its antioxidant capacity measurement confirmed that YEs‐pretreated resveratrol effectively increased its antioxidant capacity from 3.9% to 94.3%, thus reducing the wound gap in HaCaT cells, with a maximum rate of 60.2% after 24 h and complete closure after 48 h. To maximize its antioxidant property, resveratrol was incorporated into microparticles (size ranging between 20 and 30 μm) through spray drying to treat diabetic wounds. Eroğlu et al (2015) showed that resveratrol‐loaded hyaluronic acid (HA)‐dipalmitoyl phosphatidylcholine (DPPC) microparticles could increase the cell proliferation of human dermal fibroblast cells, which might be related to increase glutathione (GSH)/oxidized glutathione (GSSG) ratio.…”
Section: Beneficial Effects and Underlying Mechanisms Of Resveratrol ...mentioning
confidence: 99%